Study protocol of a multi-center RCT testing a social-cognitive intervention to promote volunteering in older adults against an active control - Warner, Lisa M.; Jiang, Da; Chong, Alice Ming-Lin; Li, Tianyuan; Wolff, Julia Katharina; Chou, Kee-Lee (BMC Geriatrics, 2019)
Background: Volunteering could be a win-win opportunity for older adults: Links between volunteering and societal improvements as well as older adults' own health and longevity are found in several observational studies. RCTs to increase volunteering in older adults are however sparse, leaving the question of causality unanswered. This study protocol describes a theory-based social-cognitive intervention with multiple behavior change techniques to increase volunteering among community-dwelling older adults in Hong Kong. Methods: In a parallel group, two-arm, randomized controlled trial, an initial N = 360 are assigned to receive either the volunteering intervention or the active control intervention (parallel content targeting physical activity). The primarily outcome measure is self-reported volunteering minutes per month at baseline, six weeks, three months and six months after the intervention. Participants in the treatment group are expected to increase their weekly volunteering minutes over time as compared to participants in the control group. Possible active ingredients of the intervention as well as mental and physical health outcomes of increased volunteering are investigated by means of mediation analyses. Discussion: Like many industrialized nations, Hong Kong faces a rapid demographic change. An effective psychological intervention to encourage retirees to engage in formal volunteering would alleviate some of the societal challenges a growing proportion of older adults entails.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Behavior change techniques; Older adults; Randomized-controlled trial; Study protocol; Theory-based social-cognitive intervention; Volunteering